MENGUJI KEABSAHAN RITUAL: ANALISIS HERMENEUTIKA TRADISI SIRAMAN KENDARAAN BARU MASYARAKAT SUNDA KAMPUNG KEMANISAN - Ahmad Ramadhani Chaidir; Rohmat Hidayatullah; Muhammad Alif (ADISAM PUBLISHER, 2026)
This study studied the tradition of flushing new vehicles that took place in the Sundanese community of Kemanisan Village, Sukawana Village, Curug District, Serang City, Banten Province. This tradition is carried out as a way to express gratitude for the blessings of owning a vehicle and ask for safety and blessings. The purpose of this research is to check the truth and validity of the ritual with a hermeneutic method, especially with the living hadith approach, which is to see how the teachings of the Qur'an and the Sunnah of the Prophet Muhammad ﷺ are understood, interpreted, and applied in the cultural practices of the community. This research uses a qualitative method with a field research approach. The data was obtained through in-depth interviews with community leaders, religious leaders, RT chairs, and residents of Kemanisan Village who were directly involved in the ritual of flushing new vehicles. In addition, participatory observation and document collection were carried out to fully understand the ritual procession, its symbolic meaning, and its social and religious functions.